Understanding the prolonged impact of online sexual abuse occurring in childhood - Schmidt, Felipa; Varese, Filippo; Bucci, Sandra (Frontiers in Psychology, 2023)
There has been a rapid increase in prevalence rates of online sexual abuse (OSA). Existing research has highlighted the negative impact OSA can have on victims. However, there is a gap in understanding the long-term impact of OSA when it occurred in childhood. This qualitative study comprised interviews with eight female participants aged 18-28 years recruited in UK NHS Trusts, and via mental health charities, University bulletins and social media. Each participant self-reported having experienced abuse through either the production or dissemination of sexual material online. Results showed that the longer-term impact of OSA was multi-fold, including negative impact on sense of self and broader interpersonal relationships, and significant impact on the participants' mental health, including experiences of self-harm, anxiety, and low mood. Likewise, participants discussed long-term apprehension to taking images and the added fear and worry that their sexual images were distributed online. Seven participants had received mental health support but only two recounted a positive experience when receiving support for OSA. Future research using a quantitative longitudinal design is needed to further explore the prolonged impact of OSA. Clinical implications of the research 2 This is a provisional file, not the final typeset article highlight the need for support services to assess the impact of OSA and interventions that target OSA experiences.